Sistem Inventarisasi Berbasis Web Menggunakan Metode Rapid Application Development - Romantika Sirait; Aris Gunaryati; Ben Rahman (Peneliti.net, 2023)
Hkbp Taman Mini is a church located in the east of Jakarta, in Cipayung, Cipayung District, to be precise. Until now the inventory in this church is still manual and information dissemination still uses paper media. This makes record keeping inefficient and inconvenient for church officials to record church inventories. To overcome these problems, we need an information system that can be used by church officials easily, accurately and precisely to create efficiency in recording church inventory and make it easier for congregations or donors in the future. Therefore, a website-based church asset information system with MYSQL database and hypertext preprocessor (PHP) was created. In designing this web-based inventory information system, the authors use the Rapid Application Development (RAD) method. It is hoped that this system will be the best solution for solving problems in managing inventory at the HKBP Taman Mini church. Using managed data computing technology reduces the risk of data loss and errors in data processing faster. To find out user satisfaction with the system created by the author, a usability test was carried out in the form of the System Usability Scale (SUS) by distributing questionnaires to 43 respondents. There are 10 statements in the questionnaire, and respondents will assess them with a choice of values ​​from 1 to 5 for each statement. Questionnaire results were obtained and a total score of 82 was calculated.